Pengaruh Brand Ambassador dan E-Wom terhadap Brand Image Pelembab Pond’s: - Leilani, Elvina Rosa; Kusnanto, Danang (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to investigate the impact of brand ambassadors and electronic word-of-mouth (E-WOM) on the brand image of Pond's moisturiser products. A descriptive and verification approach method was used in this study, which was combined with a quantitative approach. The questionnaire was directed to 347 respondents who are followers of the @pondsindonesia Instagram account. The results of the analysis show that the use of Brand Ambassadors and E-WOM has a positive impact on Pond's Brand Image. Furthermore, it was found that Brand Ambassadors have a more dominant influence in shaping consumers' positive perceptions of the brand. This research provides a deeper understanding of how the influence of marketing elements such as Brand Ambassadors and E-WOM can affect brand image on social media platforms. Keywords: Brand Ambassador; E-Wom; Brand Image